AB0374 ADALIMUMAB DISCONTINUATION IN PATIENTSWITH RHEUMATOID ARTHRITIS AFTER ACHIEVING SUSTAINED REMISSION. (June 2019) - Demidova, Natalia; Savushkina, Natalia; Galushko, Elena; Gordeev, Andrey
Abstract : Background: the most important factor in the progress of pharmacotherapy of RA was the widespread implementation of therapy with biological disease-modifying antirheumatic drugs (bDMARD). Recently, the issues of optimizing the management of patients have attracted more and more attention. First of all, we are talking about the possibility of reducing the dose and the abolition of bDMARD with the maintenance of remission ("biological-free remission"). Objectives: to assess whether adalimumab (AD) can be gradually discontinued during continuous methotrexate (MTX) use in patients with early rheumatoid arthritis (ERA). Methods: Within the REMARCA (the Russian study of methotrexate and biological agents in early active arthritis) study, the investigators examined 20 patients (17 women and 3 men; median age, 51 [41.5; 56] years) with ERA (disease duration, 10 [5.5; 20] months; DAS28, 5.17 [4.37; 6.51]; 85% of the patients were seropositive for rheumatoid factor and 85% for anti-cyclic citrullinated peptide antibodies. All the patients received subcutaneous MTX 25 mg/week. Twelve weeks after beginning therapy with MTX, due to its inefficiency, ADA was added according to the standard scheme. Clinical and laboratory data was analyzed just before the therapy (point-3 months), then at the term of 6 (n=20), 12 (n=17), 24(n=17) and 36 (n=17) months. To assess the effectiveness of therapy, indices of activity DAS28, CDAI and SDAI were used. The everyday life functioning of the patient was assessed quantitatively using the Russian version of the HAQ questionnaire. Results: At week 24, with the combined therapy of methotrexate and adalimumab, about 75% of patients have reached remission/low disease activity: the median DAS28 was 3.0 [1.65; 3.73]; 85% of the patients achieved remission or low disease activity. After 3 months of ADA therapy, high or moderate disease activity remained in 3 (15%) patients; median DAS28 was 4.4 [4.3; 6.1]; the drug was discontinued in them due to ineffective therapy. After 12-month follow-up, low DAS28 scores were observed in 5 (29.4%), DAS28 remission was in 12 (70.6%) of the 17 patients who continued ADA treatment; after 24 months, all the 17 patients were noted to have remission. After achieving sustained remission (≥ 6-month duration during ADA therapy), there was a carefully controlled reduction (titration) in the dose of ADA with its complete discontinuation, by maintaining remission at 36-month follow-up; the median DAS28 was 1.6 [1.4; 2.2]. The disease duration up to 1 year and functional class reduction to I in the first year of observation (or=46, 2; 95% CI 1, 870-1141, 178; P=0.019 and or=44, 2; 95% CI 1, 795-1088, 143; P=0.02) were identified as predictors of maintaining long-term remission after the discontinuation of ADA. RF positivity and the presence of erosion initially determined the impossibility of ADA withdrawal. (fig.1 ) Remission maintenance Conclusion: In most patients with early rheumatoid arthritis, early induction of remission can be maintained after stopping the biologic therapy, under condition that the therapy was carried out by a combination of bDMARD and methotrexate. The maintenance of remission after discontinuation of ADA therapy was influenced by the duration of the disease and the depth of remission. Disclosure of Interests: None declared